Evaluating graphing quadratic worksheet on visual thinking classification: A confirmatory analysis - Rina Oktaviyanthi; Ria Noviana Agus (IKIP Siliwangi and I-MES, 2023)
Applying a graphing quadratic worksheet as a medium for learning the concept of a Quadratic Function clearer is an alternative instrument to accommodate the needs of developing students' mathematical visual thinking. In implementing graphing quadratic worksheet should show details of the dominant and recessive visual thinking classification aspects that develop in students. Classification of dominant and recessive aspects of visual thinking needs to be completed to determine stages in improving the worksheet and learning instructions that are applied especially to recessive aspects. Therefore, there is a need to evaluate the factors and trace the classification aspects of visual thinking that developed in students after practicing the graphing quadratic worksheet. The purpose of this research is to determine the categorization aspects of visual thinking in graphing quadratic worksheet items that develop and do not develop in students. Confirmatory factor analysis was employed as a research method on 12 sub-variables from the three classifications of visual thinking. As research data, 93 student records were used. Four main factors were formed as a result of the confirmatory factor analysis procedure, with the top two factors, namely factors 1 and 2, completely representing each aspect of the visual thinking classification and achieving the factor loading significance criteria. The implication is that the variables developed in the graphing quadratic worksheet for each aspect of the visual thinking classification have a strong relationship with the visual thinking ability overall. Enhanced by a cumulative variance value for factors 1 and 2 specifically 56.88% of the total 81.78% for all factors. Thereby it can be said that the categorization aspect of visual thinking that develops in students after implementing a graphing quadratic worksheet is achieved sensibly.